answersLogoWhite

0

I'm guessing that's 18x3 + 29x2 + 3x. That factors to x(2x + 3)(9x + 1)

18x3 + 29x2 + 3x factor x

= x(18x2 + 29x + 3) write 29x as 27x + 2x

= x(18x2 + 27x + 2x + 3) group by two and factor each group

= x[(18x2 + 27x) + (2x + 3)]

= x[9x(2x + 3) + 1(2x + 3)] continue factoring

= x(2x + 3)(9x + 1)

Or since (18)(3) = 54 and (27)(2) = 54 then write:

= x(18x2 + 29x + 3)

= x[(18x + 27)/9][(18x + 2)/2]

= x(2x + 3)(9x + 1)

User Avatar

Wiki User

12y ago

Still curious? Ask our experts.

Chat with our AI personalities

BeauBeau
You're doing better than you think!
Chat with Beau
RafaRafa
There's no fun in playing it safe. Why not try something a little unhinged?
Chat with Rafa
ViviVivi
Your ride-or-die bestie who's seen you through every high and low.
Chat with Vivi

Add your answer:

Earn +20 pts
Q: How do you factor the trinomial completely 18x3 29x 3x?
Write your answer...
Submit
Still have questions?
magnify glass
imp